MODIFIKASI PERILAKU MELALUI TEKNIK TOKEN ECONOMY UNTUK MENINGKATKAN PERILAKU TANGGUNG JAWAB ANAK USIA DINI - Nia Indah Pujiati; Tina Hayati Dahlan (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2017)
This study aims to design and examine the behavior modification program using a technique token economy to improve responsible behavior of children in kindergarten Ar-Rahman Sukahening District of Tasikmalaya District Academic Year 2016/2017. Behavior modification program designed by the study of the symptoms of lack of responsible behavior, the factors causing low responsible behavior, their lack of responsible behavior, and the need for programs to improve the behavior. This study uses a quantitative approach with quasi experimental method and pretest-posttest control group design. In general, the behavior of the responsibility for early childhood and kindergarten groups Ar-Rahman Sukahening District Academic Year 2016/2017 in middle category. There is a difference between the value pretest nd post-test children after the program. Thus it can be interpreted that behavior modification programs through effective technique token economy to improve responsible behavior of children.